Pengaruh Partisipasi Politik Dalam Pemilu 2024 - Silvilia, Frisna; Enjelia, Maya (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Political participation in general elections is a key element in the dynamics of a country's democracy. This research aims to explore the influence of political participation on the outcomes of the 2024 general elections. Through meticulous literature review, factors affecting political participation such as education level, socio-economic status, access to political information, and the role of information technology and social media are deeply analyzed. Findings indicate that political participation is influenced by these complex factors. Furthermore, the research discusses the implications of these findings for policy development and strategies to enhance political participation and strengthen the process of democratization in the future. The results provide valuable insights into the modern political dynamics and the challenges and opportunities in building a more inclusive and responsive political system to the interests of the society.